Complete chamber music for strings - Mendelssohn Bartholdy, Felix 1809-1847 (Audite, 2012)
On the heels of their extremely successful Shostakovich string quartet project the Mandelring Quartet now embark on another ambitious project: the complete string chamber music of Felix Mendelssohn Bartholdy. The first volume in the anticipated set, this recording features the early string quartets that would prove Mendelssohn to be not only remarkably adept in the Romantic vernacular, but an imaginative, sophisticated musical narrator
Super audio compact disc (hybrid)
Program notes and notes on the performers in English and German (23 p. : port.) inserted in container
Keywords: String quartets; CD